2019
DOI: 10.15252/emmm.201809711
|View full text |Cite
|
Sign up to set email alerts
|

Opposite microglial activation stages upon loss of PGRN or TREM 2 result in reduced cerebral glucose metabolism

Abstract: Microglia adopt numerous fates with homeostatic microglia ( HM ) and a microglial neurodegenerative phenotype ( MG nD) representing two opposite ends. A number of variants in genes selectively expressed in microglia are associated with an increased risk for neurodegenerative diseases such as Alzheimer's disease ( AD ) and frontotemporal lobar degeneration ( FTLD ). Among these genes are progranulin ( GRN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 77 publications
19
106
0
Order By: Relevance
“…We show here that DAM signatures correlate with increased phagocytic uptake both in murine Npc1 -/microglia and in human NPC macrophages. Similarly, in LSD caused by granulin loss of function (Grn -/-) (Gotzl et al, 2018, Gotzl, Mori et al, 2014, DAM signatures correlated with increased microglial phagocytosis (Gotzl, Brendel et al, 2019). Surprisingly, microglial cells in AD acquire DAM signatures (Butovsky & Weiner, 2018, but display impaired phagocytic function , Hickman, Allison et al, 2008, Krabbe, Halle et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that DAM signatures correlate with increased phagocytic uptake both in murine Npc1 -/microglia and in human NPC macrophages. Similarly, in LSD caused by granulin loss of function (Grn -/-) (Gotzl et al, 2018, Gotzl, Mori et al, 2014, DAM signatures correlated with increased microglial phagocytosis (Gotzl, Brendel et al, 2019). Surprisingly, microglial cells in AD acquire DAM signatures (Butovsky & Weiner, 2018, but display impaired phagocytic function , Hickman, Allison et al, 2008, Krabbe, Halle et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, it is currently unclear whether sTREM2 itself may have essential functions in either a cell‐autonomous manner or a non‐cell‐autonomous manner (Ulland et al , ; Zhong et al , , ). Moreover, although a loss of function as caused by certain risk variants of TREM2 disables microglia, relegating them to a homeostatic state (Mazaheri et al , ), absence of progranulin (PGRN) has the opposite consequence, namely arresting microglia in a disease‐associated state (Gotzl et al , ). Strikingly, both opposite phenotypes are deleterious to brain health, and absence of either TREM2 or PGRN causes similar brain‐wide disturbances in energy metabolism as measured by FDG‐PET (Gotzl et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although a loss of function as caused by certain risk variants of TREM2 disables microglia, relegating them to a homeostatic state , absence of progranulin (PGRN) has the opposite consequence, namely arresting microglia in a disease-associated state (Gotzl et al, 2019). Strikingly, both opposite phenotypes are deleterious to brain health, and absence of either TREM2 or PGRN causes similar brain-wide disturbances in energy metabolism as measured by FDG-PET (Gotzl et al, 2019). Careful investigation of how Trem2 activity over time correlates with microglial function and additional data elucidating the impact of TREM2 antibody immunomodulatory activity on microglia in vivo will further improve our understanding of the chronic effects of enhanced TREM2 function and potential for efficacy in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of M4 glycolytic metabolism, it is interesting to speculate on the origin of the reduced fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) signal observed in AD brain. Recent animal model work has suggested that loss of a proper microglial response through mutations in either TREM2 or PGRN leads to reduced cerebral glucose metabolism 95 , and that normal astrocyte function is also important for brain glucose uptake 96,97 . Therefore, it is possible that the failure of a proper astroglial compensatory or protective response in AD may lead to general neuronal metabolic failure in susceptible brain regions, as assessed by the FDG-PET signal, and cognitive deterioration.…”
Section: Discussionmentioning
confidence: 99%